Eight steps towards the socialisation of the Semantic Web. (1st January 2012) - Morato, Jorge; Fraga, Anabel; Andreadakis, Yorgos; Sanchez-Cuadrado, Sonia
The web presents an autonomous evolution that could be optimised having moved towards a more formalised semantic. Web 2.0 and the Semantic Web are approaches that target the improvement of the web through mechanisms for sharing information and resources. This document argues that Web 2.0 is not an immature stage of the Semantic Web but an orthogonal dimension of another web aspect, the semantic. Unfortunately, both dimensions are not independent; the more developed a semantic representation of a system is, for being more useful for the Semantic Web, the more distant it is to the Web 2.0. A semantic system highly formalised is less intuitive and less usable for users. The different possible evolutions are: the convergence of both webs, their coexistence and the autonomous evolution of the social web towards other semantic solutions. In order to enable a real Social Semantic Web, eight proposals are sited and discussed.